Using proton pump inhibitors increases the risk of hepato-biliary-pancreatic cancer. A systematic review and meta-analysis - Wence Zhou; Wence Zhou; Xinlong Chen; Xinlong Chen; Qigang Fan; Haichuan Yu; Wenkai Jiang; Wenkai Jiang (Frontiers Media S.A., 2022)
Background: More and more studies are focusing on the adverse effects and damage caused by PPI abuse, we carried out a systematic review and meta-analysis for assessing whether the proton pump inhibitor (PPI) leads to hepato-biliary-pancreatic cancer.Methods: PubMed, EMBASE and Web of Science were searched until 1 July 2022, 25 studies (17 case-control and 8 cohort studies; 2741853 individuals) included in this study. Pooled Odd Ratios (ORs) were used for random effect models. Sensitivity analysis and dose-response analysis, subgroup analysis were all conducted.Results: The aggregate OR of the meta-analysis was 1.69 (95% confidence interval (CI): 1.42-2.01, p = 0.01) and heterogeneity (I2 = 98.9%, p < 0.001) was substantial. According to stratified subgroup analyses, the incidence of hepato-biliary-pancreatic cancer was associated, expect for study design, study quality and region. Risk of hepato-biliary-pancreatic cancer is highest when people is treated with normal doses of PPI. The risks decrease and become insignificant when the cumulative defined daily dose (cDDD) increases.Conclusion: The use of PPI may be associated with an increased risk of hepato-biliary-pancreatic cancer. Hence, caution is needed when using PPIs among patients with a high risk of hepato-biliary-pancreatic cancer.